Optical hybrid electric and magnetic B1-phase with Landau Lifshitz approach - Körpınar, Talat; Körpınar, Zeliha (Elsevier GmbH, 2021)
In this study, we derive different characterization for hybrid electric and magnetic flow B1-density of hybrid B1-magnetic particles by hybrid frame in ordinary space. Also, we construct some new optical hybrid conditions of hybrid electric and magnetic B1-phase with hybrid optical fields. We construct hybrid magnetic Lorentz B1-flux for hybrid fields with hybrid Landau Lifshitz approach. Finally, electric and magnetic B1-phases of hybrid B1-surface are presented in uniform magnetic B1-surfaces by optical results with hybrid Landau Lifshitz approach. © 2021 Elsevier GmbH
Keywords: Hybrid electric and magnetic flow density; Hybrid frame; Hybrid Landau Lifshitz approach; Optical hybrid physics